2007
DOI: 10.1089/aid.2007.0102
|View full text |Cite
|
Sign up to set email alerts
|

HIV Type 1 Subtype C and CB Pol Recombinants Prevail at the Cities with the Highest AIDS Prevalence Rate in Brazil

Abstract: HIV-1 B is predominant in Brazil, but HIV-1 C has increasingly been reported in the south of the country. However, many samples clustering with clade C are actually a recombinant, with a small B segment at RT (CRF31). Samples (209) from the three cities with the highest aids prevalence rate are analyzed. Partial polymerase sequences from HIV RNA made it possible to determine HIV clades and recombination patterns and to identify primary drug resistance mutations (DRMs). The incidence was estimated with a BED as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
36
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 23 publications
13
36
0
2
Order By: Relevance
“…In terms of molecular diversity, our results corroborate previous studies that also reported a large dominance of subtype C (ϳ65%) in SC state (30)(31)(32)(33) and a more diverse epidemic in RS state, mainly because of the high prevalence of BC mosaic forms in the latter (ϳ25%) (34)(35)(36). In both states, a low prevalence of subtype F1 and BF1 recombinants (ϳ3%) was observed, while this frequency can reach up to 20% in northern regions of Brazil (37,38) and 40% in Argentina (39).…”
Section: Discussionsupporting
confidence: 91%
“…In terms of molecular diversity, our results corroborate previous studies that also reported a large dominance of subtype C (ϳ65%) in SC state (30)(31)(32)(33) and a more diverse epidemic in RS state, mainly because of the high prevalence of BC mosaic forms in the latter (ϳ25%) (34)(35)(36). In both states, a low prevalence of subtype F1 and BF1 recombinants (ϳ3%) was observed, while this frequency can reach up to 20% in northern regions of Brazil (37,38) and 40% in Argentina (39).…”
Section: Discussionsupporting
confidence: 91%
“…Intriguingly, a single C-related sequence with unresolved classification and belonging to a native Italian homosexual man, strongly correlated to a group of sequences described in Apulia (Monno et al, 2012) and in France , and closely related to those described by other authors in Brazil (Brígido et al, 2007;Gräf and Pinto, 2012;Passaes et al, 2009a,b;Santos et al, 2006). Furthermore, the detection of such URFs-BC in three different geographic areas with no evidence of epidemiological link together with a local divergent evolutionary pathway, could represent a potential candidate for a novel CRF_BC profile, although a whole genome sequencing is mandatory to definitely confirm this evidence.…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, a preponderance of subtype C was detected among males with recent infection in Curitiba, and the overall incidence in this study was of 2.86 persons/years (95%CI: 1.04-4.68). Similar results were obtained for the two Santa Catarina cities, that presented an overall incidence estimate of 2.6 persons/year (95%CI: ±0.8) 56 , in a virological scenario where subtype C predominates. Considering the WHO criticisms 30 about the sensitivity and specificity of the BED-CEIA to estimate HIV incidence in epidemiological scenarios including non-B HIV-1 subtypes, in a preliminary study we proposed a criterion based on the matching results of two assays (BED-CEIA and Avidity index) aiming to improve the accuracy of these serological approaches to estimate HIV incidence rates 57 .…”
Section: Application Of Serological Methods To Estimate Hiv-1 Incidensupporting
confidence: 81%
“…More recently, BED-CEIA has been employed in Brazil for estimating HIV incidence and to assess the molecular characterization of newly identified HIV-1 infections in people seeking HIV diagnosis in voluntary centers for counseling and testing in Rio de Janeiro 54 , and Curitiba (Paraná State) 55 , and in a Public Health Laboratory serving communities with high prevalence of HIV infection in Santa Catarina State (Camboriú and Itajaí) 56 . Indeed, a preponderance of subtype C was detected among males with recent infection in Curitiba, and the overall incidence in this study was of 2.86 persons/years (95%CI: 1.04-4.68).…”
Section: Application Of Serological Methods To Estimate Hiv-1 Incidenmentioning
confidence: 99%